Psychological training and support for law enforcement officers in a hybrid war - S.S. Andrienko (Економіка, управління та адміністрування)
The article examines the psychological aspects of training and support for law enforcement officers in a hybrid war. The importance of psychological resilience and readiness to act in extreme conditions increases under martial law, when police officers face numerous emergencies that require immediate response and the ability to make informed decisions under pressure. Psychological training of law enforcement officers includes the development of self-control, emotional and stress management, and quick decision-making in critical situations. This aspect of training is extremely important for ensuring the stable and effective work of law enforcement officers who provide assistance to the population under stressful and dangerous conditions. The article discusses in detail modern methods of psychological support, which include regular trainings that simulate realistic combat scenarios. This allows police officers to learn how to act effectively under high stress and cooperate with other team members to achieve success in critical situations. Particular attention is paid to the provision of first aid to victims, which allows law enforcement officers not only to effectively perform their duties, but also to maintain public trust in government agencies. The article also addresses the issue of long-term psychological support for law enforcement officers, which involves the introduction of a system of professional assistance for officers working in the combat zone. An important component of this support is the prevention of the development of post-traumatic stress disorders and other mental disorders that may affect the overall level of security and efficiency of the service. Psychological training of police officers in hybrid warfare is a key element in ensuring their ability to act effectively, while maintaining their own mental health and helping the community they protect.